Passive Stretching Intervention for Upper Back Muscle Imbalance: A Focus on the Rhomboid Muscle in Adults - Sandhya Kresnajati; Riki Edo Saputro; Aziz Amrulloh; M Syahrul Muafi; Dicky Budhi Setiawan (Universitas Negeri Semarang, 2025)
Adults are increasingly experiencing upper back muscle imbalances, particularly rhomboid muscle tightness, often due to prolonged sitting and poor posture. This study aimed to evaluate the effectiveness of a single passive stretching session in relieving rhomboid muscle tightness in adults. A one-group pretest-posttest quasi-experimental design was employed using pre-existing data from Klinik Satu Sehat Semarang, which included 13 adults aged 18 to 59 years. Each participant underwent a single passive stretching session, and measurements of shoulder movement and muscle tightness were taken before and after using a goniometer and the Visual Analog Scale (VAS). A paired t-test revealed a statistically significant reduction in muscle tightness (p = 0.004), with an average decrease of two VAS points. Additionally, shoulder retraction range of motion increased by an average of 6 degrees (p = 0.001). Passive stretching of the rhomboid muscle effectively improves shoulder mobility and reduces upper back stiffness in adults within a single session, making it a practical method for addressing muscle problems caused by poor posture and applicable in rehabilitation and prevention programs.